2019
DOI: 10.1002/ijgo.13028
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum hemorrhage care bundles to improve adherence to guidelines: A WHO technical consultation

Abstract: Objective To systematically develop evidence‐based bundles for care of postpartum hemorrhage (PPH). Methods An international technical consultation was conducted in 2017 to develop draft bundles of clinical interventions for PPH taken from the WHO's 2012 and 2017 PPH recommendations and based on the validated “GRADE Evidence‐to‐Decision” framework. Twenty‐three global maternal‐health experts participated in the development process, which was informed by a systematic literature search on bundle definitions, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 24 publications
0
87
0
Order By: Relevance
“…A conceptual framework was developed to clearly identify the role and possible cost consequences of using uterine tamponade in the management of atonic PPH (Fig. 1), informed by current WHO guidance on PPH prevention and management 4 . Extracted data were summarized using tables, and brief narrative summaries of principal results and differences between studies were constructed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A conceptual framework was developed to clearly identify the role and possible cost consequences of using uterine tamponade in the management of atonic PPH (Fig. 1), informed by current WHO guidance on PPH prevention and management 4 . Extracted data were summarized using tables, and brief narrative summaries of principal results and differences between studies were constructed.…”
Section: Methodsmentioning
confidence: 99%
“…1), informed by current WHO guidance on PPH prevention and management. 4 Extracted data were summarized using tables, and brief narrative summaries of principal results and differences between studies were constructed. The currency and price year applicable to measures of costs in each study are reported alongside measures of costs, incremental costs and incremental costeffectiveness.…”
Section: Data Synthesismentioning
confidence: 99%
See 3 more Smart Citations